Measuring Students' Perceptions of ICT Use in English Listening in Online Class - Ramadhani, Andi Alyana; Amin, H. Bahrun; Sangkala, Ismail (Journal of Computer Interaction in Education, 2019)
This research aimed to find out students’ perceptions of ICT used by teachers and ICT competencies for teacher in teaching listening at the third grade of SMK Negeri 2 Makassar. This research used a quantitative method, the instruments used observation, questionnaire and interview. The observation used to observe and see the ICT used by the teacher, questionnaire is used to determine students' perceptions of ICT used by teachers in listening class and interview use to see standard teacher competencies in using ICT at the third grade of SMK Negeri 2 Makassar. The sample was taken by using Purposive Sampling Technique. The compilation results show that students' perceptions of teachers who use ICT can be said to be sufficient. It can be seen that the minimum value is 47, the maximum value is 70. Then the mean value is 58.62, the median value is 59 and the standard deviation is 5.88. In order to determine the number of interval classes to be calculated using the Sturges formula (Sugiyono, 2009) which is 1 +3.3 Log n, where n is the number of samples in the study. So that it can be obtained 1 + 3.3 Log 35 = 4.84 and rounded up to 5. The data range is 70 - 47 = 23. By knowing the data range, we can find out the length of the interval class, namely 23/5 = 4.6. The frequency distribution of students' perceptions of the use of ICT by teachers in listening to English in online classes, Based on the table above, it shows that the greatest frequency for ICT use scores is in the interval 51.6 – 56.2 as many as 10 respondents and at intervals of 60.8 – 65.4 as many as 9 respondents .